Intimate Bureaucracies - readies, dj (punctum books, 2012)
Intimate Bureaucracies is a history from the future looking backward at our present moment as a turning point. Our systems of organization and control appear unsustainable and brutal, and we are feeling around in the dark for alternatives. Using experiments in social organization in downtown New York City, and other models of potential alternative social organizations, this manifesto makes a call to action to study and build socio poetic systems. One alternative system, the Occupy movement, has demands and goals beyond the specific historical moment and concerns. This short book/manifesto suggests that the organization and communication systems of Occupying encampments represent important necessities, models, goals, and demands, as well as an intimate bureaucracy that is a paradoxical mix of artisanal production, mass-distribution techniques, and a belief in the democratizing potential of social media.